Peer-assisted reading programs for EFL low-proficiency learners - Azimova, Maftuna Ilkhom qizi; Surmanov, Sardor Egamovich (The Lingua Spectrum, 2026)
This paper investigates the efficacy of Peer-Assisted Reading (PAR) strategies for low-proficiency English as a Foreign Language (EFL) learners within a technical university context. Specifically targeting students from the faculties of Economics, Aerospace Technology, and Material Science at ’TIIAME’ National Research University, the study proposes a collaborative pedagogical framework to enhance reading comprehension and vocabulary acquisition. According to Krashen’s Affective Filter Hypothesis, negative emotions like anxiety, low motivation, or lack of confidence can block language learning. Working with peers in a structured way helps reduce these barriers by offering social support, shared responsibility, and quick help during reading, which gives students more chances to learn from meaningful input. Drawing on social interdependence theory and recent research on reading anxiety, the paper argues that structured peer interaction – combined with the use of Graded Readers and digital vocabulary tools – can mitigate the affective filter and improve engagement. Preliminary findings suggest that PAR significantly aids in bridging the proficiency gap for engineering and economics students, fostering both linguistic competence and the soft skills essential for their future professional careers.